Association between physical activity, cardiometabolic risk factors and vitamin D in children and adolescents: a systematic review - Patricia Ribeiro Paes Corazza; Maiara Cristina Tadiotto; Derick Andrade Michel; Jorge Mota; Neiva Leite (Revista Brasileira de Atividade Física e Saúde)
This systematic review aimed to synthesize evidence of cross-sectional studies on the associations between physical activity, cardiometabolic risk factors and vitamin D concentrations in children and adolescents. The search was performed in PubMed, SciELO, LILACS, Scopus, MEDLINE and SPORTDiscus. Cardiometabolic risk factors included obesity, insulin resistance, systemic arterial hypertension and unfavorable changes in the lipid profile (low levels of high-density lipoprotein, elevated low-density lipoprotein and triglycerides). Cross-sectional design studies published between 2007 and 2019 were included whether they evaluated the relationship between vitamin D and physical activity and/or vitamin D and cardiometabolic risk factors. Fourteen studies were selected, involving 8340 children and adolescents. The main results found were a significant inverse relationship between vitamin D levels and cardiometabolic risk factors. All studies (n = 8) that tested association between physical activity and 25-hydroxyvitamin D (25 (OH) D) concentrations showed a significant and direct relationship between them. In addition, nine out of eleven studies that tested the association between 25 (OH) D and body mass index reported an inverse and significant relationship between 25 (OH) D and obesity. In conclusion, sufficient concentrations of vitamin D are related to a more favorable cardiometabolic profile, and children and adolescents who are obese or insufficiently active have a higher risk of present hypovitaminosis D.